Kee Thuan Chye, Can We Save Malaysia, Please! Singapore: Marshall Cavendish Editions, 2014. 296 pp. ISBN 978-981-4561-23-5 - Ahmad, Khairil Izamin (International Islamic University Malaysia, 2015)
I trust that Kee Thuan Chye would approve it if I were to assert that Malaysian politics, at present, particularly since the publication of his last book which I reviewed in this journal, is marked by a dizzying increase in political bullshitting. Kee likes the word bullshit, even though the book under review, Can We Save Malaysia, Please!, does not contain that word in its title. However, this is not the only reason why I believe he would agree with such a characterisation of the country’s political sphere. The way politics is being played out at the moment, i.e., the constant political bullshitting which is dished out to the Malaysian public on a daily basis, marks the crossroads at which the country has arrived. Can We Save Malaysia, Please! superbly captures this uncertain moment. And, crucially, Kee reminds his fellow Malaysians that a real change is long overdue in the country. At a time when their “political leaders are more bent on other pursuits” (18), it is up to concerned Malaysians from all walks of life to be the movers of this change.